2021
DOI: 10.3390/ijerph18116008
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Respiratory Diseases Decreased during the COVID-19 Pandemic in South Korea

Abstract: Infectious respiratory diseases are highly contagious and very common, and thus can be considered as one of the leading causes of morbidity and mortality worldwide. We followed up the incidence rates (IRs) of eight infectious respiratory diseases, including chickenpox, measles, pertussis, mumps, invasive pneumococcal disease, scarlet fever, rubella, and meningococcal disease, after COVID-19 mitigation measures were implemented in South Korea, and then compared those with the IRs in the corresponding periods in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…We identified six studies, including two European studies from Italy and Sweden, describing the trends of several infectious diseases, including pertussis, before and after implementing their respective COVID-19 mitigation measures [21][22][23][24]. Although the power of these studies was much lower compared with ours (lower duration of surveillance and description of a maximum of ca 1,500 cases, vs 19,039 cases in our study), they found a decrease in pertussis cases following the implementation of mitigation measures, with reductions ranging from 28% to 87% [21][22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 71%
“…We identified six studies, including two European studies from Italy and Sweden, describing the trends of several infectious diseases, including pertussis, before and after implementing their respective COVID-19 mitigation measures [21][22][23][24]. Although the power of these studies was much lower compared with ours (lower duration of surveillance and description of a maximum of ca 1,500 cases, vs 19,039 cases in our study), they found a decrease in pertussis cases following the implementation of mitigation measures, with reductions ranging from 28% to 87% [21][22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 71%
“…The transmission of SARS-CoV-2 mainly occurs through the airways by the saliva droplets emission and by the aerosols generated by respiration [ 3 , 4 ], while a minor role is associated with contact with contaminated surfaces [ 5 , 6 , 7 , 8 ]. According to the main route of transmission, the use of face masks to cover mouth and nose proved to be among the most effective tools for limiting the spread of SARS-CoV-2 [ 9 ] resulting in a significant decrease of several infectious respiratory diseases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Danfeng et al [23] also showed that the frequency of co-infection between the ages of 3 and 6 years was higher than that in other age groups. Respiratory virus infection is considered highly contagious, making it easy for young people with weak immunity to become infected [7,24].…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of the COVID-19 pandemic in December 2019, mitigation measures, such as compliance with personal hygiene regulations, social distancing, and environmental cleaning to prevent the spread of COVID-19, have affected the overall reduction of infectious diseases [7,8]. However, despite the decreasing trend, the number of cases with mumps reported to the Korea Disease Control and Prevention Agency in 2021 were 9,708, the second-most after 20,923 cases of chickenpox.…”
Section: Introductionmentioning
confidence: 99%